Dexmedetomidine attenuates neuropathic pain in chronic constriction injury by suppressing NR2B, NF-κB, and iNOS activation - Feng Liang; Miao Liu; Xin Fu; Xueying Zhou; Peng Chen; Fanglei Han (Elsevier, 2017)
The effective treatment of patients suffering from neuropathic pain remains challenging. Dexmedetomidine (DEX) possesses anti-inflammatory activity. However, the role of DEX in neuropathic pain is still unclear. The aim of the present study was to examine DEX an α2-adrenoceptor agonist could improve pain hypersensitivity and reduce inflammatory in a chronic constriction injury (CCI) model of the sciatic nerve in Sprague-Dawley rats. Dex was intrathecally administrated 1-h after operation. The paw mechanical withdrawal threshold (MWT) and paw withdrawal thermal latency (PWTL) were measured on day 1 before operation and on days 1, 7, 14 and 21 after operation, respectively. On day 21, all the rats were decapitated to collect the L4-6 segments of the spinal cord to examine IL-1, TNF-α, IL-6, NR2B, NF-κB, and iNOS mRNA levels using RT-PCR. The postoperative MWT and PWTL were significantly decreased in CCI, and DEX groups as compared to those before surgery and Sham group (P < 0.05). And DEX reversed this trend (P < 0.05). Interleukin 1 (IL-1), tumor necrosis factor α (TNF-α), IL-6 mRNA expression significantly increased postsurgery in CCI group as compared to that of Sham group (P < 0.05); DEX blocked increased IL-1, TNF-α, IL-6, N-methyl-D-aspartate (NMDA) receptor 2B (NR2B), nuclear factor κB (NF-κB), and inducible isoform of nitric oxide synthase (iNOS) mRNA levels (P < 0.05). DEX may alleviate neuropathic hypersensitivity and inflammation partially by inhibiting NR2B, NF-κB, and iNOS expression in the spinal cord of rats with neuropathic pain resulting from CCI of the sciatic nerve. Keywords: Neuropathic pain, Dexmedetomidine, Inflammation, Rat